2012
DOI: 10.5194/acp-12-4923-2012
|View full text |Cite
|
Sign up to set email alerts
|

Global stratospheric hydrogen peroxide distribution from MIPAS-Envisat full resolution spectra compared to KASIMA model results

Abstract: Abstract. MIPAS-ENVISAT full resolution spectra were analyzed to obtain a global distribution of hydrogen peroxide (H 2 O 2 ) in the stratosphere. H 2 O 2 acts as reservoir gas for the HO x family (= H+OH+HO 2 ) and thus, observations of H 2 O 2 provide a better understanding of the HO x chemistry in the atmosphere. A retrieval approach based on constrained least squares fitting was developed and applied to small dedicated spectral analysis windows with maximum H 2 O 2 information and minimum contribution of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…(2002), previously used in the LMD GCM (Lefèvre et al., 2004). The use in photochemical models of a fast H 2 O 2 formation rate at low temperatures, such as that of JPL 2003, does not seem recommended as it leads to a strong overestimation of H 2 O 2 in the terrestrial stratosphere (Versick et al., 2012). By contrast, a slow H 2 O 2 formation rate at low temperatures, such as that of Christensen et al.…”
Section: Simulating the O3‐h2o Relationmentioning
confidence: 99%
“…(2002), previously used in the LMD GCM (Lefèvre et al., 2004). The use in photochemical models of a fast H 2 O 2 formation rate at low temperatures, such as that of JPL 2003, does not seem recommended as it leads to a strong overestimation of H 2 O 2 in the terrestrial stratosphere (Versick et al., 2012). By contrast, a slow H 2 O 2 formation rate at low temperatures, such as that of Christensen et al.…”
Section: Simulating the O3‐h2o Relationmentioning
confidence: 99%
“…HO 2 can undergo selfreaction upon surfaces of mineral dust, which is thought to result in the generation of H 2 O 2 (Matthews et al, 2014), whose two predominant removal pathways are photolysis and reaction with OH (Versick et al, 2012):…”
Section: Introductionmentioning
confidence: 99%
“…[256][257][258][259][260] The study revealed the details and energetics of the dissociative electron transfer process at the molecular level, but its relevance for the stratospheric ozone depletion could not be established by laboratory experiments. 250 Hydrogen peroxide, H 2 O 2 , plays an important role in many areas of atmospheric and interstellar chemistry as a source of HO x radicals 261,262 and oxidation agent contributing to the aerosol nucleation. 45,46,151,153 We have investigated the electron attachment to hydrogen peroxide (H 2 O 2 ) adsorbed on Ar N and ice (H 2 O) N nanoparticles.…”
Section: Electron Attachmentmentioning
confidence: 99%